A clinical pilot study of Resection Process Map: A novel virtual hepatectomy software to visualize the resection process, case series. (November 2019) - Uchida, Yuichiro; Taura, Kojiro; Nakao, Megumi; Uemoto, Shinji
Abstract: Background: Preoperative simulation of liver resection to visualize the intraoperative cutting process, including liver deformation, may help surgeons to more accurately implement hepatectomy. We developed a novel simulation software called Resection Process Map (RPM). The present study was performed to evaluate the feasibility and efficacy of RPM as a tool for preoperative simulation and surgical education for liver surgery. Materials and methods: Twenty-four patients who underwent anatomical hepatic resection at our institute from February 2017 to May 2018 were enrolled in this study. The time needed to prepare RPM for each patient was recorded. The imaging similarity between the image provided by RPM and the intraoperative photograph was evaluated with the Dice similarity coefficient and locational displacement of the vessels of interest. The surgeons completed questionnaires. The educational effect was assessed by a survey administered to medical students who attended clinical clerkship at our department from October 2017 to December 2018. Results: The time required to prepare the dataset for RPM was 199 ± 20 s after completion of operative planning in SYNAPSE VINCENT. The Dice similarity coefficient for surface similarity was 0.85 ± 0.06, where 1.00 indicates perfect concordance. The mean positional displacement of the vessels of interest was 8.7 ± 6.7 mm. Medical students' application of RPM significantly improved their survey score (use vs. non-use of RPM, 6.5 vs, 4.6, respectively; p < 0.001). Conclusion: RPM allows for preoperative simulation of hepatectomy and might be helpful for many surgeons. RPM is also useful for education of medical students. Highlights: Resection Process Map; a novel hepatectomy simulation software. Contain information regarding the planned resection line. Realize the intraoperative parenchymal deformation. Allows operators to divide the liver in a step-by-step manner on computer screen.